Pengaruh Budaya Organisasi Pada Hubungan Antara Penerapan Good Government Governance dan Kinerja Pegawai - Bismantara, Anak Agung Ngurah Mahaputra; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p11, 2019)
The purpose of this study is to obtain empirical evidence of  Organizational Culture as a moderator between the application of Good Government Governance and Employee Performance. The sample is determined using the Slovin method. The population of this research is 61 people who work in Dinas Penanaman Modal Denpasar City. The method of data collection is done using the questionnaire method and the data analysis techniques used are factor analysis and moderated regression analysis. Based on the analysis it was found that Good Government Governance had a positive effect on Employee Performance, and Organizational Culture was able to strengthen the effect between Good Government Governance and Employee Performance. Keywords: Good Government Governance, Organizational Culture, and Employee Performance